Comparative study of structural, mechanical and electrical properties of Ni0.8Co0.1Cu0.05Mn0.05Fe2O4 prepared from different combustion routes. (1st April 2013) - Jadhav, P.S.; Patankar, Ketaki K.; Mathe, V.L.; Puri, V.
Abstract : Comparative studies on the structural, mechanical and electric properties of Ni0.8 Co0.1 Cu0.05 Mn0.05 Fe2 O4 prepared by solid state combustion and solution combustion routes were studied. The X‐ray diffraction patterns reveal the cubic spinel phase formation with an extra Fe2 O3 phase for Ni0.8 Co0.1 Cu0.05 Mn0.05 Fe2 O4 prepared by the solid state combustion method in contrast to the single cubic spinel phase formation for ferrites obtained from other routes. Scanning electron microscopic images show loosely agglomerated grains with comparatively large grain size for Ni0.8 Co0.1 Cu0.05 Mn0.05 Fe2 O4 prepared by solid state combustion, whereas there are well defined grains with distinct grain boundaries and smaller grain size for solution combustion route ferrite. Micro‐strains calculated from XRD show a higher value for ferrite obtained from the solution combustion method route. The Young's modulus also show higher values for ferrite prepared from solution combustion, asserting comparatively high spontaneous magnetostriction in the magnetic domains of these ferrite particles. The fourier transform infrared study reveals the octahedral and tetrahedral bond formation in the authors' ferrites prepared by both methods. Despite comparatively higher values of electric resistivity for solid combustion route ferrite, the authors' combustion route ferrite can serve as a competent phase for application in transducer or sensor devices.